EFFECT OF SPRAYING ASCORBIC ACID AND SALICYLIC ACID ON THE GROWTH AND YIELD OF FABA BEAN(VICIA FABA L.) GROWING IN SALT SOIL - Al-Alawy, Hasan Hadi; Al-Tamimy, Wisam H.; Falih, Shaymaa T. (Diyala Agricultural Sciences Journal, 2020)
A pot experiment was conducted in the Department of Soil Sciences and Water Resources at the College of Agriculture / Diyala University for the agricultural season 2018-2019. The seeds were planted in saline soils (EC = 8.1 dS m-1 ). The results showed that the treatments used in the research exceeded the comparison treatment in improving the growth and yield characteristics of the faba bean plant. All the treatments were significantly increase of plant height, fresh weight of shoot, dry weight of shoot and fresh weight of the pod comparison with control, all treatments were significantly increase of dry weight of pod except for the treatment of the first concentration of salicylic acid (SA1). While the treatment of the first level of both acids (AsA1SA1) and the interaction between the second concentrations of ascorbic acid with the first concentration of salicylic acid (AsA2SA1) were significantly superior compared to the comparison treatment in increasing the number of branches / plant.